Q: How do you solve by substitution y equals x-1?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

17

Algebraic equations with two variables will need two equations to be able to solve it. Then, you can solve it with either substitution, adding/subtracting them together, or graphing! Those are the basic steps... For example: An instance of substitution: 2x + 1 = y + 2 x + y = 3 You could isolate y in the second equation to equal y = 3-x. Then in the first equation, substitute y with what it equals to 2x + 1 = 3-x+2 Then you can solve for x!

X = 135 and y = 15 Solved by addition and substitution

To solve the following equation by substitution, we need to have the equal sign. This will help us group the knowns and the unknowns.

If: x+y = 8 and 2x-y = 5 Then by adding the equations together: 3x = 13 or x = 13/3 By substitution into the original equations: x = 13/3 and y = 11/3

Related questions

x+y=5

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 => 3 = 3x => 1 = x So by substitution: x = 1 and y = 3

-2

y= -4x-7 y=3x 3x= -4x-7 3x+4x=7 7x=7 x=1

17

This is not Calculus.y=7(Already solved)substiute y=7 into y=8xtherefore 7 = 8xtherefore x = 7/8

By definition: 4x-10 = 5-x 4x+x = 5+10 5x = 15 x = 3 and y = 2

Substitution property.

-3x = 3 + y 3 + y - 5y = -21 -4y = -24 y = 6 x = -3

4x-y=2, thereforey=4x-2sub y into 3x+2y=6...3x+8x-4=611x=10x=10/11

Algebraic equations with two variables will need two equations to be able to solve it. Then, you can solve it with either substitution, adding/subtracting them together, or graphing! Those are the basic steps... For example: An instance of substitution: 2x + 1 = y + 2 x + y = 3 You could isolate y in the second equation to equal y = 3-x. Then in the first equation, substitute y with what it equals to 2x + 1 = 3-x+2 Then you can solve for x!